“Filling the Void in the Web Space”- Microbiological Perspective of Toe Web Space Infections in a Tertiary Care Hospital - Gopi, Dr. Anjana; Samreen, Dr. Faiza; Jain, Dr. Swati; C.K., Dr. Madhulatha (International Journal of Innovative Research in Medical Science, 2017)
Toe web space infections are the most common superficial dermatoses of the feet. They are often unnoticed and progress to cause discomfort. There is lack of enough evidence on the microbiological profile and antifungal susceptibility pattern. Settings and Design: A prospective study was conducted between August 2015 to February 2017 in the Department of Microbiology at a tertiary care hospital. Methods and Material: 200 samples were collected from interdigital spaces of Dermatology outpatients and inpatients. Bacterial and fungal pathogens were isolated and identified using conventional laboratory techniques. Antifungal susceptibility testing was done to determine the Minimum inhibitory concentration (MIC) by E-test. A small representative sample of Fusarium isolates were subjected to speciation by PCR and their MIC was determined by broth microdilution method for comparison. Statistical analysis used: p value was determined by Chi square test using SPSS software. Results: Our study demonstrated a male preponderance of 59 %, mostly between 41 to 50 years. Both the feet were affected in 43/48 (89.5 %) of the diabetic patients, the fourth web space being commonly involved. 198/200 (99%) of the samples were positive for either bacterial or fungal growth. There were a total of 156 fungal and 204 bacterial isolates. Out of 156 fungal isolates, Candida spp 62 (39.7 %) and Fusarium spp 50 (32 %) were the most common isolated yeast and mould respectively and 38 (24.3 %) dermatophyte species were isolated. Results of E-test and broth microdilution were comparable. Voriconazole and amphotericin B had lower MIC. Out of 204 bacterial isolates, Staphylococcus aureus 56 (27.4 %) and Pseudomonas aeruginosa 44 (21.5 %) were the most common isolates. Conclusions: A good microbiological diagnosis would assist in the better alleviation of the symptoms and provide accurate treatment of web space infections.